Description of the fatty acids of the eggs of Araucanas and Marans hens - Hernández-Guzmán, Filogonio Jesús; Rodríguez-Ortega, Alejandro; González-Cerón, Fernando; Mendoza-Pedroza, Sergio Iban; Rodríguez-Ortega, Leodan Tadeo; Crosby-Galván, María Magdalena (Ecosistemas y Recursos Agropecuarios, 2021)
.The fatty acid profile of the egg is an important aspect of consumer health. The objective of this work was to describe the fatty acids present in the blue egg of Araucanas and brown of Marans hens. The blue egg was similar in weight, length and          width to the brown one. The brown egg showed slightly higher protein content than the blue egg, while the blue egg had higher ethereal extract than the brown egg. The content of oleic acid and docosahexaenoic acid was higher in the brown egg, however, the blue one had a higher content of linoleic and linolenic acid with respect to the brown egg. In conclusion, the blue egg of Araucanas hens and the brown egg of Marans hens contain fatty acids, which according to the consulted literature, are beneficial for human health.